A pH-responsive and magnetically separable dynamic system for efficient removal of highly dilute antibiotics in water. (1st March 2016) - Liu, Wanpeng; Ma, Jianqing; Shen, Chensi; Wen, Yuezhong; Liu, Weiping
Abstract: In order to control the antibiotic-related crisis and reduce the negative impacts on the environment and human health, it is urgent to develop effective technologies to eliminate residual antibiotics in water. Herein, we successfully fabricated a novel, pH-responsive and magnetically separable dynamic system for micropollutant adsorption and oxidation degradation in graphene oxide (GO)/nanoscale zero-valent iron (nZVI) composite with macroscopic structure. The pH-responsive self-assembly behavior of GO/nZVI composite was explored. The macroscopic structure of GO/nZVI composite serves as an excellent adsorbent for antibiotic removal in water. The adsorption process is fast and highly efficient even in high salty and humic acid containing water under acid to neutral conditions. After removal antibiotics, GO/nZVI composite is conveniently separated by magnetic system and put into alkaline solution (pH > 9) for adsorbent regeneration. Interestingly, it is found that at pH > 9, GO/nZVI composite disassembles partly upon increasing pH values, leading to the elution of antibiotics for efficient antibiotics degradation by ozonization. More importantly, this pH-responsive GO/nZVI system exhibits high removal efficiency, high stability, reusability and easily separation, making it a promising method for treatment of water with micropollutants. Graphical abstract: Highlights: A novel pH-responsive and magnetically separable dynamic system was proposed. GO/nZVI composite with macroscopic structure is successfully fabricated. This system can effectively remove antibiotic micropollutants in water. It shows high stability, regeneration and reusability, especially easily separation. It is a promising method for treatment of water with low concentration contaminants.